Water toxicity and sediments and benthic community from the estuary of the Itanhaém river, (SP Brazil): basis for environmental education - Lima Silveira, Fabiana; Seriani, Robson; Romano, Priscilla; Voietta Pinna, Fernanda; Moledo de Souza Abessa, Denis (O Mundo da Saúde, 2006)
The Estuary of the Itanhaém River is situated at Baixada Santista, located on the Southern Coast of São Paulo State (23°50’-24°15’S; 46°35’- 47°00’W). This area is now the object of human settlements. Although the estuary seems to be low degraded, the discharge of pollutants into this river may put aquatic life in danger, as well as threaten fish resources. Considering that contaminants tend to sink to the bottom, where they accumulate, this study aimed to evaluate the environmental quality of this estuary, by using whole sediment toxicity and water toxicity tests, physical chemical analyses and the evaluation of the benthic community. Such parameters can be used to establish environmental education programs, with the purpose of showing the risks caused by pollutants and how pollution can influence the well-being of local populations. Three sampling stations were established in the lower estuary. Toxicity and the absence of fauna in station 1 were attributed to sediment grain size (thick sands), whereas station 3 showed evidences of natural enrichment. The sediment from station 2 showed evidences of degradation, due to toxicity. The quality of waters was relatively better, with both bioassays and physical chemical parameters indicating good conditions. However, the low survival rate of Nitocra sp exposed to the sample from station 1 may be a sign of toxicity, indicating the need for more detailed studies. The results provided new information for the conservation of this river, and may be used in further environmental education programs conducted to this region.